Study of water quality for rain water harvesting systems on roof material - Abdul Mu’iz, Embong (2017)
Rainwater harvesting have a potential to be next sources of clean water besides tap water. Two objectives of this study are to study water quality of potential roof material for rainwater harvesting systems in UMP buildings and to suggest an appropriate water treatment in order to improve quality of harvested rainwater. In this study, three different roof types were investigated, which is Clay roof, Metal deck roof and Concrete flat roof and ambient rainwater as a control sample. Rainwater sample was collected in 3 different rain events. Water quality in this study is determined by doing tests on 9 parameters which is; pH, temperature, conductivity, total suspended solid (TSS), turbidity, nitrate, nitrite, total coliform and Escherichia Coli (E-Coli). The proposed treatment for harvested rainwater is chlorination, UV filtration, Sand Gravel filters and reverse osmosis. All these guidelines gained from the WHO Drinking Water Standards 1993 and National Water Quality Standards of Malaysia.